High resolution multi-nuclear 1 and 2D NMR characterization of stannous halide complexes of Rh(I/III) in aqueous and non-aqueous solutions - Barkhuysen, Shani (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.